Environment and Society Concepts and Challenges (Palgrave Studies in Environmental Sociology and Policy, 2018)
This book offers a critical analysis of core concepts that have influenced contemporary conversations about environment-society relations in academic, political, and civil circles. Considering these conceptualizations are currently shaping responses to environmental crises in fundamental ways, critical reflections on concepts such as the Anthropocene, metabolism, risk, resilience, environmental governance, environmental justice and others, are well-warranted. Contributors to this volume, working across a multitude of areas within environmental social science, scrutinize underlying worldviews and assumptions, asking a common set of key questions: What are the different concepts able to explain? How do they take into account society-environment relations? What social, cultural, or geo-political biases and blinders are inherent? What actions or practices do the concepts inspire? The transdisciplinary engagement and reflexivity regarding concepts of environment-society relations represented in these chapters is needed in all spheres of society-in academia, policy and practice-not the least to confront current tendencies of anti-reflexivity and denialism. .